Clinical guidelines of the Russian gastroenterological association and the Russian society on study of the liver on diagnostics and treatment of cholestasis - V. T. Ivashkin; Ye. N. Shirokova; M. V. Mayevskaya; Ch. S. Pavlov; O. S. Shifrin; I. V. Mayev; A. S. Trukhmanov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
.